APPLICATION OF THE DYNAMIC STANDARD MODEL IN OPERATIONAL PLANNING - Babich , V.; Babich-Gaury, A.V. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article discusses the applied aspect of the use of mathematical models in the operational management of a company, in particular in the process of operational planning. Approbation of the model based on the method of dynamic programming for a specific object of study will be carried out. The key integral indicators that affect the efficiency of company management are determined. These indicators allow for determining the strengths and weaknesses in the main business processes, adjusting tactical objectives, and improving the decision-making process. Integral indicators can serve as quantitative guidelines when setting strategic goals and, on the basis of them, motivational operational tasks can be set, which are assessed at the end of the calendar period. The dynamic programming model allows you to determine the priority sequence of changes in controllable factors according to the level of growth rate to achieve an effective result within the framework of achieving the strategic goal of profitable sustainable growth of the company.